Sosialisasi Penggunaan Aplikasi Tracker Di Sma IT Al-Husnayain Panyabungan - Siregar, Yenni Amalia; Siregar, Evitamala; Fadilah, Rizki; Aisyah; Siregar, Sri Utami Kholilla Mora (Yayasan Kajian Riset Dan Pengembangan Radisi, 2024)
Current technological advances have given birth to various innovations, especially in the field of digital learning. One of them is a tracking application which is very useful in helping carry out a physics practicum. The aim of implementing this community service program is to train students on how to use the tracker application to facilitate the implementation of physics practicum which can be carried out in class 10 of SMA IT AL-Husnayain Panyabungan. Based on observations, it appears that this tracker application is something new for students, making it very easy to carry out practical activities in class. Evaluations and testimonials from students reveal that the practicum use of this tracker application provides students with the opportunity to receive active learning that is centered on themselves, especially in creating practicum designs and analyzing practicum results and this tracker application can provide innovation in the implementation of physics practicum in schools.